Islam and human rights: a fiqh muasarah approach to universal values / Ahmad Husaini Abd Karim … [et al.] - Abd Karim, Ahmad Husaini; Muhamad Shaifuddin Shah, Muhammad 'Amirul Hazim; Azizi, Muhammad Hakim; Sh Abdul Halim, Sh Mohd Ashaari (2023)
It is important to understand that Islam places human rights as a form of God's gift to his caliph on this earth. Islam is a comprehensive religion, and its teachings are in line with human nature and include all aspects of human life. It should be explained that Islam is not just a ritualistic religion but a complete and perfect way of life. Unfortunately, there are groups in society who disparage this aspect of the perfection of Islam by labeling Islam as a narrow, stagnant religion that does not keep up with the new currents of thought that exist today. Therefore, this assignment explores a fiqh muasarah approach to universal value. There are have three main objectives that are been stated in this study which is this study will explain about human right from an Islamic perspective. besides, the study also will explore what is the method of fiqh muasarah approach towards the universal value to ensure that every people get the same right. Lastly, to explains how to relate the prinsip of maqasid shariah towards universal values. There are also several issue that has been discussed in this study. In order to achieve the three objectives, qualitative methods are used to obtain accurate reference sources such as primary data and secondary data.